Factors Associated with Active Aging at Payung Sekaki Health Center Pekanbaru City - chaliza bebby ewys; Kiswanto Kiswanto; Jasrida Yunita; Mitra Mitra; Kamali Zaman (STIKes Hang Tuah Pekanbaru, 2021)
Quality healthy elderly refers to the active aging concept, namely the aging process that remains physically, socially and mentally healthy so that they remain prosperous throughout life. Many factors are related to the activity of the elderly such as: sports, income and gender with education as a confounding variable because it has two unique relationships, namely it is positively related to the exposure variable and positively related to the exposed variable (active aging). The purpose of the study was to determine the health factors associated with active aging. This type of quantitative analytic research, using a cross sectional design. The study population was the elderly group registered in each Posyandu in the Payung Sekaki Community Health Center. The sample is 121 respondents. Data was collected by distributing questionnaires. Data analysis used Chi Square test and multiple logistic regression. The results of the analysis show that there is a significant relationship between exercise, income, gender and education with active aging. It is better for the government to consistently carry out efforts to improve social welfare for the elderly, so as to support healthy aging and active aging.